PENGARUH PENGGUNAAN PARAMETER NUMBER SCAN AVERAGE TERHADAP SIGNAL TO NOISE RATIO DAN SCAN TIME PADA PEMERIKSAAN MAGNETIC RESONANCE IMAGING: STUDI LITERATURE REVIEW - Kadek Agus Cahya Pramana; Ni Putu Rita Jeniyanthi; I Bagus Gede Dharmawan (JRI (Jurnal Radiografer Indonesia), 2022)
Background : Signal to Noise Ratio (SNR) is a comparison of the magnitude of the signal amplitude and the magnitude of the amplitude of noise an MRI image that can be used to measure the quality of an MRI image. SNR can be increased by increasing the value of the number scan average (NSA). By increasing the NSA, the SNR will also increase, the scan time will be longer and cause motion artifacts. The purpose of this study was to determine the effect of using the parameter Number Scan Average on the Signal to Noise Ratio and Scan Time on examinations using Magnetic Resonance Imaging modalities. Methods: This study uses a descriptive qualitative method with a study approach literature review regarding the effect of using the parameter Number Scan Average on the Signal to Noise Ratio and Scan Time in the examination using Magnetic Resonance Imaging modalities. Results: The use of variations in NSA values ​​has an effect on SNR and scan time. Giving high value of the NSA will increase the value of the SNR in the image but, the scan time will be longer which affects the quality of the resulting image.